Efeito do espaçamento de plantio nas propriedades da madeira em árvores jovens de eucalipto - Brito, Alice Soares (2017)
The aim of the study was to evaluate the effect of planting spacing on the production and wood properties of clones of E. grandis and of the hybrid E. grandis x E. urophylla, at 4-year-old. The trees were selected according to the mean diameter of each experimental plot and after the harvest, discs in diameter at breast height (DBH) and in the positions 0 (base), 25, 50, 75 and 100% of the commercial height were removed for analysis. The data were evaluated through regression analysis and the results showed that planting spacing explained part of the variations in basic density, dry mass, vessel diameter and frequency and wall thickness of the fibers in at least one of the three clones studied. However, the heartwood/sapwood relation; percentage and permeability of heartwood and sapwood; length and fraction of fiber wall; extractive, lignin and ash contents, as well as the gross calorific value of the wood were not influenced by planting spacing in any of the three genetic materials at the age in question. In general, planting spacing did not clearly interfere with wood properties and did not influence the proportion and permeability of the heartwood and sapwood.